Husk rice used in the pack carburizing process of the AISI 1020 steel - F. Llano M., J.; A. Pérez R., E.; Cárdenas D., A. (International Journal of Engineering and Technology, 2019)
Carburizing is a heat treatment used to increase the carbon concentration on the surface of specimen of steel, in order to obtain a high hardness and a toughness core. One of the methods used to achieve these characteristics is the pack carburizing using charcoal or mineral coal. In this work, the heat treatment of pack carburizing on the SAE 1020 mild steel (disks 75 mm in diameter and 10 mm thick) is carried out using rice husk as a carbon source. The heat treatment was carried out at a temperature of 950° C with a soaking time of 7 hours. In addition, the results of the experimentation were compared with the results obtained with the traditional charcoal. In general, it was observed in the microstructural analysis and in the surface hardness that the charcoal, unlike the rice husk, provides better characteristics in terms of a greater penetration of the carbon in the piece and in the achievement of greater hardness.